Transferability of microsatellite markers among nine pine species - Sandoval-Padilla, Isaac; Contreras-Toledo, Aremi Rebeca; Guzmán, Luis Felipe; Amaro González, Blanca Amalia; Cortés-Cruz, Moisés (Instituto de Ecología, A.C., 2021)
There are 94 species of conifers distributed in Mexico, from which Pinus L. species are the most abundant with 49 species. Nevertheless, the genetic diversity studies on Mexican populations of pines are limited, particularly those including molecular markers considered species-specific, such as microsatellites (SSR). The initial cost for their identification is high when the species’ genome has not been sequenced, as well as the designing of primers that allow the amplification of the SSR regions.  However, an alternative is the assessment of SSR in related species. The objective of this study was to evaluate the transferability of SSR markers developed for P. taeda in different pine species. Genomic DNA was isolated from P. ayacahuite, P. cembroides, P. devoniana, P. hartwegii, P. lumholtzii, P. luzmariae, P. patula, P. jeffreyi and P. pseudostrobus, based on CTAB method (ionic detergent cetyltrimethylammonium bromide) from liophylized tissue. The markers were selected based on linkage group (LG), motif and position within the LG. Finally, fragments were amplified by PCR and products were quantified. Thirty-seven markers (95%) amplified in at least one of the nine species. From those, 27 (69%) amplified in more than 50% of the species. These markers were present in the 12 LG. Amplification of more than 75% was observed for P. jeffreyi, P. pseudostrobus and P. devoniana. The transferability of these markers represents an alternative for genetic diversity studies across pine species.